Implementation of Public Order Policies in the Handling of Homeless People in the City of Cirebon - Leni Rohida; Tia Nuraeni (Pelopor Publikasi Akademika, 2026)
The number of homeless people in public spaces in Cirebon City indicates that the implementation of Local Regulation No. 13 of 2019 on Public Order has not been effective. The purpose of this study is to examine how the policy on handling vagrants in Cirebon City is implemented from the perspective of George C. Edward III's implementation theory, which includes communication, resources, disposition, and bureaucratic structure. This study employs a qualitative approach, utilizing in-depth interviews with the Public Order Agency (Satpol PP), the Social Services Agency, and the target group of the vagrancy policy. Additionally, field observations and documentation were conducted. The results of the study reveal that although coordination between implementing agencies has been carried out, it has not achieved all of its objectives. The main factors hindering policy implementation include limited resources, a lack of supporting facilities such as shelters, and poor vertical communication with the target group. Despite the good commitment of the implementers, the homeless population still does not fully experience the impact of the policy. The research findings suggest that while the policy has been implemented, its execution has not been optimal in some areas, and strengthening is required in the elements of resources, operational mechanisms, and social empowerment services. This research also contributes to public administration studies on the implementation of social policies at the local level and recommends improving policy integration and the provision of supporting facilities.